Impact Of Timely Bcr-abl1 Monitoring Before Allogeneic Stem Cell Transplantation Among Patients With Bcr-abl1-positive B-acute Lymphoblastic Leukemia - Siew Lian Chong; Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Tze Shin Leong; Jenq Tzong Tan; Kian Boon Law; Siong Leng Hon; Rui Jeat Fann; Sen Mui Tan (Korean Society of Hematology, 2024)
Indexed by WOS/SCOPUS